Multivessel spontaneous coronary artery dissection with angiographic documentation before and after the acute event. Issue 4 (June 2015) - Matsumura, Mitsuaki; Mintz, Gary S.; Green, Philip; Fall, Khady N.; Sherman, Warren; Dizon, José M.; Maehara, Akiko
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.